2016
DOI: 10.15252/emmm.201506046
|View full text |Cite
|
Sign up to set email alerts
|

Inducing mitophagy in diabetic platelets protects against severe oxidative stress

Abstract: Diabetes mellitus (DM) is a growing international concern. Considerable mortality and morbidity associated with diabetes mellitus arise predominantly from thrombotic cardiovascular events. Oxidative stress‐mediated mitochondrial damage contributes significantly to enhanced thrombosis in DM. A basal autophagy process has recently been described as playing an important role in normal platelet activation. We now report a substantial mitophagy induction (above basal autophagy levels) in diabetic platelets, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
119
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(122 citation statements)
references
References 73 publications
3
119
0
Order By: Relevance
“…A collection of fresh blood and isolation of washed mouse platelets were conducted as described previously (Lee et al, 2016; Feng et al, 2014; Ouseph et al, 2015). Briefly, the Fundc1 fl/fl ::Pf4 Cre+ mice (8 to 10 weeks old) and their Fundc1 fl/fl ::Pf4 Cre- littermates were anesthetized with pentobarbital (70 mg/kg, i.p.).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A collection of fresh blood and isolation of washed mouse platelets were conducted as described previously (Lee et al, 2016; Feng et al, 2014; Ouseph et al, 2015). Briefly, the Fundc1 fl/fl ::Pf4 Cre+ mice (8 to 10 weeks old) and their Fundc1 fl/fl ::Pf4 Cre- littermates were anesthetized with pentobarbital (70 mg/kg, i.p.).…”
Section: Methodsmentioning
confidence: 99%
“…Platelets were prepared as described previously (Lee et al, 2016; Feng et al, 2014; Ouseph et al, 2015). Washed mouse platelets (3 × 10 8 /ml) resuspended in modified tyrode buffer (MTB) were lysed in 2 × platelet lysis buffer (1 mM dithiothreitol, 0.15 M NaCl, 0.1 M Tris, 2% Triton X-100 and 0.01 M EGTA, pH 7.4) containing E64 (0.1 mM), 1/100 aprotinin and phenylmethylsulfonyl fluoride (PMSF, 1 mM), at a volume ratio of 1:1 on ice for 0.5 hr.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 Similarly, p53 activation induces irreversible G1/S or G2/M cell-cycle arrest, senescence, and apoptosis 15,16 but can also activate the energy sensor AMPK pathway, inhibit the mammalian target of rapamycin (mTOR) pathway, and transactivate multiple genes with pro-autophagic effects. 21 Recent studies have shown that ROS could act as cellular signalling molecules to initiate autophagosome formation and autophagic degradation, 22 whereas autophagy can reduce oxidative damage and ROS levels through removal of protein aggregates and damaged organelles such as mitochondria. 21 Recent studies have shown that ROS could act as cellular signalling molecules to initiate autophagosome formation and autophagic degradation, 22 whereas autophagy can reduce oxidative damage and ROS levels through removal of protein aggregates and damaged organelles such as mitochondria.…”
Section: Introductionmentioning
confidence: 99%